1991
DOI: 10.1152/jappl.1991.71.3.961
|View full text |Cite
|
Sign up to set email alerts
|

Absence of exercise-induced MRI enhancement of skeletal muscle in McArdle's disease

Abstract: To assess the role of glycogenolysis in mediating exercise-induced increases in muscle water as monitored by changes in muscle proton relaxation times on magnetic resonance imaging (MRI) and cross-sectional area (CSA), five patients with myophosphorylase deficiency (MPD) were compared with seven controls. Absolute and relative work loads were matched during ischemic handgrip and graded cycling, respectively. Relaxation times of active muscle did not increase after handgrip in MPD (T1: 1 +/- 14%, P greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
1
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 0 publications
5
70
1
1
Order By: Relevance
“…Second, following high-intensity resistance training, less muscle is required to lift a given absolute load, as documented by a reduction in magnetic resonance image contrast shift (29). Such a reduction in muscle recruitment is associated with an alteration in metabolic demand (1,11). Third, the kinetics of force development can also play a role in altering metabolic demand of the exercising muscle (36).…”
Section: Discussionmentioning
confidence: 99%
“…Second, following high-intensity resistance training, less muscle is required to lift a given absolute load, as documented by a reduction in magnetic resonance image contrast shift (29). Such a reduction in muscle recruitment is associated with an alteration in metabolic demand (1,11). Third, the kinetics of force development can also play a role in altering metabolic demand of the exercising muscle (36).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis revealed that pH i and % ⌬V i Ј changes both help to predict R 2i Ј changes (P Ͻ 0.05), but that V e Ј changes do not (P Ͼ 0.05). The equation resulting from this analysis is: [7] which indicates that 70% of the variance in R 2i Ј during exercise can be accounted for by intracellular pH and volume changes. None of the hypothesized physiological variables could explain the R 2e Ј changes.…”
Section: Exercise-inducedmentioning
confidence: 99%
“…Increases in interstitial volume [such as those caused by exercise (24) or leg negative pressure (18)] increase SI in T2-weighted images (6,18), although the low interstitial volume fraction diminishes the importance of these changes (4,18). Recently, Hu et al (12) showed through the injection of an extracellular contrast agent that postexercise hyperemia affects SI in T2-weighted images as well.…”
mentioning
confidence: 99%